Pediatric eosinophilic esophagitis outcomes vary with co-morbid eczema and pollen food syndrome - Sessions, Julia; Purington, Natasha; Wang, Yiwen; McGhee, Sean; Sindher, Sayantani; Goyal, Alka; Khavari, Nasim (Frontiers in Allergy, 2022)
Background: Eosinophilic esophagitis (EoE) is a chronic immune-mediated inflammatory disease characterized by eosinophil inflammation of the esophagus. It has been described as a component of the Allergic March and is often seen with other atopic diseases. Some atopic diseases, including asthma, are known to be heterogenous with endotypes that guide treatment. Similarly, we propose that EoE is a heterogenous disease with varying phenotypes and endotypes that might impact response to therapy. Methods: A single-center retrospective review of pediatric patients <18 years of age diagnosed with EoE was conducted. All gastrointestinal clinic visits and esophagogastroduodenoscopies (EGD) from disease presentation through the first three years after diagnosis were reviewed. Histologic remission rate and therapies utilized (proton pump inhibitor [PPI], topical steroid, dietary elimination) were assessed. Results: One hundred and thirty-seven patients were included, 80% of whom had at least one concurrent atopic condition at diagnosis, with food allergies being the most common (57%) followed by eczema (34%), and asthma (29%). The remission rate of the overall cohort was 65%, and by concurrent allergy, comorbid pollen food syndrome and eczema had the highest remission rates at 100% and 81%, respectively followed by asthma (62%), food allergies (62%), seasonal allergic rhinitis (60%), and history of anaphylaxis (56%). Kaplan-Meier curves for each atopic condition show that patients with eczema and pollen food syndrome achieve histologic remission faster than those without. All treatment modalities were more successful in patients with eczema than those without, and PPI was most effective treatment at inducing remission. Conclusions: In a real-world pediatric cohort, 80% of patients with EoE had an underlying atopic condition. Patients with eczema and pollen food syndrome had a swifter response and were more likely to achieve histologic remission than patients with other atopic conditions. This study suggests that EoE, like other allergic diseases, may have heterogenous phenotypes that could affect response to treatment. There is currently a knowledge gap in classifying EoE based on endotypes and phenotypes at diagnosis and correlating responses to various treatment modalities.